TESIS KINERJA KELURAHAN NOLOGATEN KECAMATAN PONOROGO KABUPATEN PONOROGO: JURNAL TESIS - Susfita Arum Lestari (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The results of the research. The performance of the Nologaten village can be seenfrom the productivity of the Lurah in providing services that is quite good wherethis is indicated by the attitude of the apparatus that still distinguishes, the abilityof the apparatus is also not maximized, and the work spirit of the Lurah whichstill has to be improved to increase the professionalism of its apparatus in publicservices. The obedience of the apparatus as the leader of the Nologaten subdistrictgovernment, in the form of service transparency, timeliness and serviceprocedures, received a poor response from the community using the services ofthe sub-district government. Discipline The previous apparatus has served and inobeying the rules for when to enter the office and finish office hours, it was foundin the field that the apparatus did not arrive and leave the office on time. Fromthe results of field research on staff, it shows that the quality is still low.Keyword: Government